Estimates of Fiscal Multipliers using MEDSEA - Noel Rapa (Central Bank of Malta, 2017)
This paper documents the fiscal extension to MEDSEA, the Central Bank of Malta DSGE model. The model contains a relatively rich fiscal sector. Decisions made by the agents in the model are affected by distortionary taxes on labour income, capital income and consumption. On the expenditure side, the model distinguishes between public sector expenditure on final goods and services, public investment, public employment as well as transfers to households. The model is used to assess the size of fiscal multipliers in a very open and small open economy such as Malta. Both transitory and permanent shocks are considered. It also allows for changes in the instrument used to finance the change in fiscal policy.
Keywords: E62; H63; 330